Exercise-Based Interventions for Internet Addiction: Neurobiological and Neuropsychological Evidence - Li, Shanshan; Wu, Qianjin; Tang, Cheng; Chen, Zichao; Liu, Li (Frontiers in Psychology, 2020)
With the increase in the number of internet users, the problems associated with excessive internet use have become increasingly obvious. Exercise as an alternative or auxiliary intervention for internet addiction has drawn much attention recently, but its neurobiological mechanisms are not completely understood. Here we reviewed the neurobiological mechanisms of exercise-based interventions against internet addiction by searching the research literature with such keywords as "exercise", "internet addiction"," hypothalamic-pituitary-adrenal axis", "neurotrophin", and "dopamine". This review summarizes advances in our understanding of the neurobiological processes through which exercise can reduce internet addiction, and our analysis strengthens the idea that exercise-based interventions can be effective in this regard. The available evidence suggests that exercise can increase the levels of neurotrophic factors, cortisol, and neurotransmitters; improve the morphology of specific parts of the central nervous system, such as by stimulating hippocampal neurogenesis; protect the autonomic nervous system; and control the reward urge. In other words, exercise appears to mitigate internet addiction by regulating the neurobiology of the central and autonomic nervous systems. In this way, exercise-based interventions can be recommended for reducing internet addiction.